Challenges of students or graduates of the Licentiate Courses of the IFMT Campus Confresa in the preparation of the Course Conclusion Work (Research, Society and Development, 2021)
The Course Conclusion Work (CCW), a mandatory requirement in most undergraduate courses, involves a scientific study, with readings, data collection and analysis, in addition to having specific standards and formats, which often cause difficulties for students. The research aimed to describe the perceptions of students or graduates of Licentiate Courses at the IFMT Campus Confresa about the challenges faced while writing their CCWs. This research, descriptive and qualitative in approach, took place in March 2021 and involved 30 participants, including senior students and graduates of Licentiate Courses at the IFMT Campus Confresa. As a data collection instrument, an electronic form consisting of 26 questions was used, with 05 open and 21 closed. Several challenges were pointed out by the research subjects, among them the most cited were the difficulty in scientific writing, understanding and use of technical standards, as well as the choice and definition of a theme. Students who were completing the CCW were asked if this pandemic period had impacts on the preparation of the CCW, most responded that it has been difficult, especially in terms of keeping the distance from the advisor, colleagues, institution, the difficulty of data collection and defense online. To conclude, it is possible to say that the CCW is a challenge for students, especially in writing and familiarization with formatting standards.